Natural resources and economic growth in Ghana - BIRITWUM, Kwabena (KDI School, 2016)
Ghana is blessed with several natural resources. The recently discovered crude oil in commercial quantities has yet to boost unsustained growth in Ghana. This study considers how Natural Resource can speed up economic growth in Ghana. It looks at examples from Botswana, Malaysia, Sweden, and Netherlands as well as other resource-rich nations and attempts to understand what they did differently. It also considers Ghana’s comparative advantage and explores opportunities beyond it. It finally comes up with deliberate policy recommendations based on empirical data available which, if implemented, will transform not just Ghana but any Resource Rich Country, especially in the West African Sub-Region.
Thesis(Master) --KDI School:Master of Public Policy,2016